2016
DOI: 10.1115/1.4034165
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Local and Average Heat Transfer Coefficients Under an Inline Impinging Jet Array, Including Jets With Low Impingement Distance and Inclined Angle

Abstract: Comprehensive impingement heat transfer coefficients data are presented with varied Reynolds number, hole spacing, jet-to-target distance, and hole inclination utilizing transient liquid crystal. The impingement configurations include: streamwise and spanwise jet-to-jet spacing (X/D, Y/D) are 4∼8 and jet-to-target plate distance (Z/D) is 0.75∼3, which composed a test matrix of 36 different geometries. The Reynolds numbers vary between 5,000 and 25,000. Additionally, hole inclination pointing to the upstream di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The influence of the inclination was too small to consider (within the error margin). Li et al [9] measured the heat transfer for inclined and orthogonal jets including jets with separation distance. They distinguished two flow regimes depending on the separation distance.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the inclination was too small to consider (within the error margin). Li et al [9] measured the heat transfer for inclined and orthogonal jets including jets with separation distance. They distinguished two flow regimes depending on the separation distance.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [43] experimentally measured perpendicular and inclined jets and found that inclined holes do not significantly alter heat transfer patterns. It is possible that the short orifices used were not long enough to provide a direction for the exiting jets.…”
Section: Factors In Jet Impingement Heat Transfer Representative Figurementioning
confidence: 99%
“…Li et al [10] studied the influence of the Reynolds number, jet-to-jet spacing, je-to-target distance and jet inclination on the local and average heat transfer coefficients under an inline impinging jet array at 5,000 ≤ Re ≤ 25,000. To measure the heat transfer coefficients, they used a Transient Liquid Crystal technique.…”
Section: Introductionmentioning
confidence: 99%